The Influence of Educational Infrastructure and Motivation on the Performance of Junior High School Teachers in Bandar Negeri Suoh District - Susilo Susilo; Ahmaludin Ahmaludin (Universitas Sang Bumi Ruwa Jurai, 2023)
Performance is a work ability or work achievement demonstrated by an employee to obtain optimal work results. There are several factors that can improve teacher performance, including salary, facilities and infrastructure, physical working environment conditions, and leadership. Supporting facilities and infrastructure will be able to assist teachers in carrying out their duties. Facilities are all equipment, materials and furniture that are directly used in the educational process at school. Apart from that, the teacher motivation factor must also be good. Therefore, the aim of this research is to determine the influence of educational infrastructure and motivation on the performance of junior high school teachers in Bandar Negeri Suoh District, West Lampung Regency, Lampung Province, both partially and simultaneously. This research uses quantitative research methods, as well as an Explanatory Survey approach. The population of this research is all junior high school teachers in Bandar Negeri Suoh sub-district, West Lampung. Determining the sample size used the Slovin formula, so that 45 teachers were obtained as research samples. The data collection technique in this research is using a questionnaire prepared using a Likert scale. The data analysis methods used are classical assumption tests and multiple linear regression analysis with coefficient of determination hypothesis tests, partial tests and simultaneous tests. Based on the research results, it was found that 1) educational infrastructure had a significant positive effect on the performance of junior high school teachers in Bandar Negeri Suoh District; 2) motivation has a significant positive effect on the performance of junior high school teachers in Bandar Negeri Suoh District; and (3) Simultaneously, educational infrastructure and motivation have a significant positive effect on the performance of junior high school teachers in Bandar Negeri Suoh District.